Respuesta :
Answer:
w = 18
Step-by-step explanation:
w+6 = 2(w-6)
w+6 = 2w-12
2w-w = 6+12
w = 18
hope it helps
Answer:
[tex] \huge \boxed {w = 18}[/tex]
Step-by-step explanation:
Distribute 2 in the bracket.
[tex]w + 6 = 2w - 12[/tex]
A constant and variable cannot add up or subtract each others. Therefore, move the same term to the same side.
[tex]12 + 6 = 2w - w \\ 18 = w[/tex]
Answer Check
Substitute w = 18 in the equation.
[tex]18 + 6 = 2(18) - 12 \\ 24 = 36 - 12 \\ 24 = 24[/tex]
Therefore w = 18 is the correct answer.